Japan: achieving UHC by regulating payment - Naoki Ikegami (BMC, 2019)
Abstract The triple goals of Universal Health Coverage (UHC) are to cover the whole population, to reduce patients' costs, and to expand coverage to all effective services, equitably available to all. This paper analyses the experience of Japan in achieving these goals, focusing on the central role played by the payment system. The payment system, or fee schedule, sets the price of services and pharmaceuticals, as well as the conditions that providers must comply with in order to receive payment. The fee schedule was first introduced following the enactment of social health insurance (SHI) in 1922. Initially, the SHI program covered only manual workers, who comprised a mere 3% of the population. However, the fee schedule of the largest SHI plan was subsequently adopted by all other SHI plans. From 1958, there has been only one fee schedule. Population coverage was achieved in 1961 by mandating all residing in Japan to enroll in SHI, thereby making everyone entitled to all the services and pharmaceuticals listed in the fee schedule. Next, co-insurance was capped to an affordable level by the introduction of catastrophic coverage in 1973. Lastly, extra billing and balance billing were explicitly restricted in 1984. The key to achieving and sustaining UHC goals in Japan lies in being able to contain costs and reallocate resources by revising the fee schedule.